Acquisition of the pluripotent and trophectoderm states in the embryo and during somatic nuclear reprogramming. (October 2017) - Jaber, Mohammad; Sebban, Shulamit; Buganim, Yosef
Abstract : How the first cell fate decision of an embryo occurs is one of the most fascinating biological questions examined over the last few decades, with numerous in vivo models proposed and many factors tested for their role in the process. In this review, we will primarily focus on the mouse model and discuss the role that transcription factors play during establishment and maintenance of the first lineage segregation in the embryo, towards inner cell mass or trophectoderm. We will also overview recent developments in somatic nuclear reprogramming into induced pluripotent stem cells, the inner cell mass (epiblast) equivalent, and into induced trophoblast stem cells, the trophectoderm equivalent, and discuss potential correspondences between the in vivo and in vitro models.